2017
DOI: 10.1152/ajpregu.00012.2017
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoiesis with endurance training: dynamics and mechanisms

Abstract: The purpose of the present study was to characterize the progression of red blood cell volume (RBCV) expansion and potential volumetric and endocrine regulators of erythropoiesis during endurance training (ET). Nine healthy, untrained volunteers (age = 27 ± 4 yr) underwent supervised ET consisting of 3-4 × 60 min cycle ergometry sessions per week for 8 wk. Plasma volume (PV), RBCV, and overnight fasting hematological markers were determined before and at ,, and of ET. In addition, plasma erythropoietin (EPO), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
98
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 66 publications
4
98
0
1
Order By: Relevance
“…The high inter‐individual variability of EPO in our data renders the difference non‐significant. The increases in EPO concentration seem to be initiated by the PV expansion and a lowered haematocrit, which is similar to what happens after 2 weeks of endurance training (Montero et al., ). There are conflicting reports on changes in resting plasma aldosterone concentrations after HA protocols (Kirby & Convertino, ; Nielsen et al., ).…”
Section: Discussionsupporting
confidence: 73%
“…The high inter‐individual variability of EPO in our data renders the difference non‐significant. The increases in EPO concentration seem to be initiated by the PV expansion and a lowered haematocrit, which is similar to what happens after 2 weeks of endurance training (Montero et al., ). There are conflicting reports on changes in resting plasma aldosterone concentrations after HA protocols (Kirby & Convertino, ; Nielsen et al., ).…”
Section: Discussionsupporting
confidence: 73%
“…The finding that only LF individuals demonstrated a higher EPO response by day 6 suggests that the EPO response is potentiated in the untrained versus trained state when humans are subjected to a similar exercise stimulus in terms of duration and relative intensity. Alternatively, an increased EPO response may serve to counteract the concurrent decrease in Hct levels which was stimulated by plasma volume expansion (Montero et al, ). This possibility, however, is not supported by the fact that the MF people expanded their plasma volume with EPO remaining unaffected and no observed correlation between the changes in Hct and EPO (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The changes in BV reported after 6-8 weeks ET (3-4 sessions week −1 ) typically range from 140 to 550 ml (Bonne et al 2014;Helgerud et al 2007;Montero et al 2017Montero et al , 2015aMontero and Lundby 2017b), whereas a meta-analysis reported a mean increase of 267 ml after ~ 15 weeks of ET (range 1-51 weeks) (Montero and Lundby 2017a). A complex interplay of mechanisms causes the BV expansion in ET that may be affected by the training program, the training status of the subjects and their nutritional status (Montero and Lundby 2018;Sawka et al 2000).…”
Section: The Magnitude Of Haematological Adaptationsmentioning
confidence: 99%